2022
DOI: 10.3389/fped.2022.951127
|View full text |Cite
|
Sign up to set email alerts
|

Rotavirus vaccination and the risk of type 1 diabetes and celiac disease: A systematic review and meta-analysis

Abstract: BackgroundRotavirus vaccination has been proven to effectively protect against rotavirus gastroenteritis. However, there are concerns about the relationship between rotavirus vaccination and the risk of autoimmune disorders. Thus, we conducted a systematic review and meta-analysis to comprehensively assess the association between rotavirus vaccination and type 1 diabetes (T1D) or celiac disease (CD) risk.MethodsA systematic review and meta-analysis were conducted to evaluate the type 1 diabetes or celiac disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 34 publications
1
1
0
Order By: Relevance
“…A review summarizing the evidence considering the association of rotavirus with T1D concluded that the connection remains unclear and there is no clear evidence for either protection or increased risk for T1D because of rotavirus vaccination ( 25 ). This is in line with a recent meta-analysis, including several of the studies mentioned above, where researchers concluded no association between rotavirus vaccine and T1D or celiac disease ( 26 ).…”
Section: Introductionsupporting
confidence: 88%
“…A review summarizing the evidence considering the association of rotavirus with T1D concluded that the connection remains unclear and there is no clear evidence for either protection or increased risk for T1D because of rotavirus vaccination ( 25 ). This is in line with a recent meta-analysis, including several of the studies mentioned above, where researchers concluded no association between rotavirus vaccine and T1D or celiac disease ( 26 ).…”
Section: Introductionsupporting
confidence: 88%
“…In addition, epidemiological and immunological studies show a possible association between rotavirus infection and autoimmune diseases, most commonly celiac disease. Thus, the rotavirus vaccines should be able to decrease this autoimmune disease-associated rotavirus infection, although it is still controversial[ 52 , 53 ].…”
Section: Driving Forces Of Rotavirus Evolutionmentioning
confidence: 99%